2023
DOI: 10.3390/antiox12071358
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Molecular Resonance Inhibits NLRP3 Inflammasome/Nitrosative Stress and Promotes M1 to M2 Macrophage Polarization: Potential Therapeutic Effect in Osteoarthritis Model In Vitro

Abstract: This study aimed to investigate the anti-inflammatory effects of Quantum Molecular Resonance (QMR) technology in an in vitro model of osteoarthritis-related inflammation. The study used THP-1-derived macrophages stimulated with lipopolysaccharide and hyaluronic acid fragments to induce the expression of inflammatory cytokines and nitrosative stress. QMR treatment inhibited COX-2 and iNOS protein expression and activity and reduced NF-κB activity. Furthermore, QMR treatment led to a significant reduction in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Concurrently, QMR notably decreased NLRP3 levels and activated caspase-1 protein expression, leading to a downregulation of IL-18 and IL-1β protein expression and secretion. Moreover, our research suggests that QMR treatment prompts a shift in macrophage polarization from the M1 to the M2 phenotype in vitro [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, QMR notably decreased NLRP3 levels and activated caspase-1 protein expression, leading to a downregulation of IL-18 and IL-1β protein expression and secretion. Moreover, our research suggests that QMR treatment prompts a shift in macrophage polarization from the M1 to the M2 phenotype in vitro [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the above, in this study we hypothesize that the treatment with QMR found in vitro [ 16 ] could, in vivo, translate into a reduction in pain in patients with symptomatic KOA due to its anti-inflammatory and regenerative action; there are no studies on this subject in the literature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation